Antiallodynic effect of propoxazepam at monoiodoacetate-induced osteoarthritis in rats - M.Ya. Golovenko; I.P. Valivodz; A.S. Reder; V.B. Larionov (Bolʹ, Sustavy, Pozvonočnik)
Background. Osteoarthritis (OA) is a chronic degenerative joint disease that affects around 654 million persons aged ≥ 40 years worldwide; it most commonly affects joints of knees, hips, hands, and feet in people and is considered to be one of the most expensive chronic conditions to treat. The purpose of this study was to assess the antiallodynic effects of orally administered propoxazepam in the monoiodoacetate-induced knee osteoarthritis (MIA) model in rats. Materials and methods. Unilateral OA was induced by an intra-articular injection of MIA (2 mg/50 μl) into the tibio-femoral joint cavity of the right hindpaw of the rat at the beginning of the experiment (on D0) under gas anesthesia (3.5% isoflurane/3 L/min). Tactile allodynia was assessed using the electronic Von Frey test 2 hours after propoxazepam administration. To determine the statistical effect of the test substance and the reference substance, data were analyzed by a parametrical t-Student test for dependent sets. The significance was estimated at levels p ≤ 0.05 and p ≤ 0.01. Results. Our findings demonstrated that at 10 and 20 mg/kg, propoxazepam induced a significant increase in the paw withdrawal threshold as compared to the vehicle-treated group (+32 and +46 %), highlighting an antiallodynic efficacy. The mean effective dose (ED50) of propoxazepam in this model using the probit-method conditions was estimated as 33.8 mg/kg on rats. Conclusions. Propoxazepam demonstrates significant antiallodynic effects in a rat model of OA (p ≤ 0.05 for doses 2 and 4 mg/kg, p ≤ 0.01 for doses 10 and 20 mg/kg), suggesting its potential as a therapeutic option for managing pain associated with this condition. However, further studies are required to explore the long-term efficacy and safety profile of propoxazepam in chronic pain management related to OA.